Kelimpahan Bakteri Vibrio sp pada Air Sampel Tambak Udang Vaname (Litopenaeus Vannamei) Berdasarkan Lokasi Tambak yang Berbeda (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Vaname shrimp (Litopenaeus Vannamei) is one of Indonesia's fishery commodities with high economic value. Vaname shrimp production in Indonesia continues to increase. However, obstacles sometimes arise in cultivation activities, such as the emergence of shrimp diseases and poor water quality. High stocking density and shrimp feeding can cause a decline in water quality. In addition, pond water quality is influenced by pond location and the surrounding environment, such as agriculture, settlements, mangroves, and the sea. This causes ponds to have different water qualities. One of the diseases that often attacks shrimp farming is caused by the bacterium Vibrio sp. The abundance of Vibrio sp. bacteria is closely related to pond water quality and the environmental conditions around the pond. The methods used were TPC testing and multiple linear regression testing. Based on the results of the study, the abundance of Vibrio sp. bacteria in pond A was the highest at 8.3 x 102, and pond C had the lowest at 3.1 x 102. Water quality testing in three different ponds showed safe limits for cultivation, except for nitrite testing. Based on the simple linear regression test, the water quality parameters that significantly affect the abundance of Vibrio sp. bacteria are pH, temperature, and nitrite.